Development of Zero Turning Radius by Using Different Independent Torque - Muhammad Asyraf, Shahrom; Mohamad Heerwan, Peeie (IEEE, 2017)
This paper is about development of zero turning radius (ZTR) by using different independent torque that given to the all tires. The main objective in this thesis is to analyze the approximate or actual zero turning radius that can be achieved by vehicle and yaw rate when the different independent torque is given to the each tire. The ZTR is existed by applied the differential torque from the motor. Meanwhile, different of torque is mean the different of rotational movement or different of torque value given by the motor. The analysis is conducted by using Matlab simulation analysis because it is very important for EVs. By using the ZTR system the vehicle can move in the narrow space and time to change the position become less. This system (ZTR) also can be applying for the light and heavy weight electrical vehicles when going for changing position in narrow with less much time.